Association of Autism Spectrum Disorder, Neuroticism, and Subjective Well-Being With Cardiovascular Diseases: A Two-Sample Mendelian Randomization Study - Sun, Xingang; Chen, Lu; Wang, Zhen; Lu, Yunlong; Chen, Miao; He, Yuxian; Xu, Hongfei; Zheng, Liangrong (Frontiers in Cardiovascular Medicine, 2021)
Background: Previous observational studies have reported an association between psychiatric traits and cardiovascular diseases (CVDs). In this two-sample Mendelian randomization (MR) study, we aimed to investigate the causality between psychiatric traits and CVDs. Methods: Single-nucleotide polymorphisms (SNPs) associated with autism spectrum disorder (ASD), neuroticism, and subjective wellbeing at genome-wide significance (P < 1×10-8) were identified from genome-wide association studies. Summary-level data of the outcomes, including coronary artery disease (CAD), myocardial infarction (MI), atrial fibrillation (AF), and heart failure (HF), were obtained from several largest datasets. The inverse-variance weighted (IVW) method was used as our main analyses to conduct this MR study. Sensitivity analyses included the weighted median, the MR-robust adjusted profile score (MR-RAPS), and the MR pleiotropy residual sum and outlier (MR-PRESSO) method. Repeated MR analyses using a more relaxed threshold (P < 1×10-6) for instruments selection and multivariable MR analyses were also applied to evaluate the robustness of results. Results: The MR analyses showed that genetic predisposition to ASD was associated with a higher risk of AF (odds ratio (OR), 1.109; 95% confidence interval (CI), 1.023-1.201; P = 0.011) and HF (OR, 1.138; 95% CI, 1.036-1.251; P = 0.007). Neuroticism was casually associated with an increased risk of AF (OR, 1.201; 95% CI, 1.037-1.392; P = 0.015), whereas subjective wellbeing had a protective effect on HF (OR, 0.732; 95% CI, 0.574-0.933; P = 0.012). No other causal association between psychiatric traits and CVDs was observed. Consistent results were obtained in sensitivity analyses. Conclusion: This study provided evidence of causal associations of ASD with a higher risk of AF and HF. Besides, neuroticism was casually associated with an increased risk of AF, and subjective wellbeing was associated with a decreased risk of HF.